Carotid intima-media thickness in patients with non-alcoholic fatty liver disease: a study from eastern part of India - Narayan, Ruchika; Ahmad, M. Shamim (International Journal of Research in Medical Sciences, 2024)
Background: Carotid intima-media thickness (CIMT) is a reliable marker of atherosclerosis and cardiovascular events. Association between CIMT with non-alcoholic fatty liver disease (NAFLD) is well known; however, such data are limited from India. This study aimed to assess CIMT in NAFLD patients compared to the healthy control, its relationship with other metabolic covariates, and predators of increased CIMT. Methods: In an observational study, involving 150 subjects (84 NAFLD and 66 healthy controls), B-mode ultrasound was used for the evaluation of CIMT. Results: The mean CIMT was significantly higher in NAFLD patients compared to the control group: 0.77±0.27 versus 0.57±0.11 mm on left side, p<0.001 and 0.79±0.22 versus 0.54±0.12 mm on right side, p<0.001. The difference was significant even after adjustment of metabolic confounders. Eight NAFLD patients had carotid plaques compared to none in the controls. The mean CIMT did not differ significantly between lean, overweight and obese subjects. A progressive increase in mean CIMT was noted with increasing grades of hepatic steatosis. High CIMT values (>95th percentile value in controls, 0.79 mm) were found in 52.3% of NAFLD. On multivariate regression analysis, age [odds ratio (OR) 1.42, p<0.001], serum HDL cholesterol [OR 0.92), p=0.02] and NAFLD [OR: 3.5, p<0.001] were found to be independently associated with high CIMT. Conclusions: NAFLD was significantly associated with CIMT which increased progressively with increasing grades of hepatic steatosis. Over half of NAFLD had increased CIMT, and NAFLD along with higher age and lower HDL- cholesterol independently predicted high CIMT values.